Penyuluhan Pemerintah Magetan Terhadap Pengetahuan Dan Tindakan Pencegahan Stunting Oleh Kader Posyandu Di Wilayah Desa Bungkuk - Andhita Risko Faristiana; Aza Maulia Puspitasari; Berliana Rahma Normalita (Lembaga Pengembangan Kinerja Dosen, 2023)
Stunting is a physical growth problem that causes children to not be able to grow as they should and causes a linear decrease in growth rate. One of the causes of stunting in Bungkuk Village is the upbringing and eating pattern taught by parents to their toddlers. In this study, we use an Asset Based Community Development (ABCD) strategy to show how changes in knowledge about stunting are influenced by health education. In conclusion, efforts to prevent and treat stunting in the community will include good knowledge as a provision. This community service approach using the ABCD method can increase public awareness about stunting. Supported by guidance and assistance provided by village health post midwives and posyandu cadres to ensure that anyone who may experience symptoms that result in stunting is immediately treated. The need for awareness and parental participation in preventing this is proven by the decline in the effectiveness of the stunting prevention work program and knowledge in Bungkuk Village.